PERANCANGAN MEDIA PROMOSI SANGGAR TARI GITO MARON ART PERFORMA SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Nareswari, Nindyaning Ayu; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2015)
Abstract : Gito Maron Art Performa is a group dance studio that tips grow, raise, and foster appreciation of the younger generation of art, the noble and strengthen the nations love of art and culture as well as understanding the noble values that must be maintained and preserved. Certainly the increasing number of dance studio in Surabaya, which can lead to competition between the dance studio that makes the Gito Maron Art Performance dance studio unknown back. In resolving the problem, the solution is to make updates promotion media was up to date on the current draft and the need for additional promotion media Gito Maron Art Performa dance studio such as web design, flyers, business cards, mini banner, poster, note book, brosur and catalogs. Promotion media can help inform effectively and efficiently to the public, in order to raise awareness of the existence of the studio Gito Maron Art Performa in regions throughout Indonesia, especially in East Java.Keywords: Design, Promotion Media, Dance Community Gito Maron Art Performa, Brand Awareness.